2020
DOI: 10.15845/praxeologi.v2i0.3067
|View full text |Cite
|
Sign up to set email alerts
|

Different Professional Ideal Types in the Inter-sectoral Management of Psychiatric Healthcare Trajectories

Abstract: Aim: To investigate how differences in types of professions and rationalities affect the management of inter-sectoral trajectories in psychiatric health care in the Capital Region of Denmark. Background: Some psychiatry users experience a lack of coherence between the mental health care treatment provided at hospitals and run by the regions, and that provided at residential psychiatric units run by municipalities. The literature points to various challenges in this field of research, related to transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, apart from the hospitals, the CMHWs in this study reported better collaboration with fellow community partners, as both of them adopted similar treatment approaches and placed greater importance on social elements such as the PMHCs’ rehabilitation into the community (Frederiksen et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, apart from the hospitals, the CMHWs in this study reported better collaboration with fellow community partners, as both of them adopted similar treatment approaches and placed greater importance on social elements such as the PMHCs’ rehabilitation into the community (Frederiksen et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is closely tied to the democratisation of discourse whereby professionals and users meet equally and respectfully. Democratisation has been a real force in modern medicine, and even though debate continues around cases where inequality and bigotry are still flagrant, the level and salience of the debate itself indicates that such issues are on the agenda [ 2 , 9 , 11 , 15 ]. Democratisation and dialogical discourses are not just methods but also interpersonal ways of meeting each other.…”
Section: Discussionmentioning
confidence: 99%
“…The professionals lack methods to work in a recovery-oriented way and to ensure coherence in efforts across psychiatric and municipal sectors [ 5 ]. Various initiatives are taken in mental health services across the sectors to promote a more recovery-oriented practice and cross-sectoral collaboration, e.g., implement open dialogue [ 6 ], flexible assertive community treatment [ 7 ], more focus on personal recovery [ 8 , 9 ], and cross-sectoral network meetings [ 10 , 11 ].…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…Governmentality reflects this practice where language is associated with technical tools, practices and institutions aimed at shaping and reshaping behavior [ 35 ]. As other studies show, the user is, however, not sufficiently involved [ 1 , 6 , 18 ] and finds that the professional paternalistic discourse deprives them of the right to influence [ 4 , 18 , 25 ]. Users’ expert knowledge is downplayed and not included in the rational language of professionals, which elevates medical knowledge, evidence and selected legislative paragraphs as steering tools.…”
Section: Discussionmentioning
confidence: 99%
“…In several Western countries and regions such as the USA, Australia, the United Kingdom and Scandinavia, user involvement has been a milestone in the health sector. Health professionals must involve users in healthcare across mental health hospitals and community mental healthcare [ 1 , 2 ]. The Health Act in Denmark emphasizes that the patient’s right to self-determination must be respected [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%